The Eye of Zoltar / 3 - Fforde, Jasper (Fforde, Jasper. Chronicles of Kazam, 2014)
Sixteen-year-old Jennifer Strange faces the impossible when the mighty Shandar emerges from his preserved state and presents her with a task that sends her and her companions on a journey from which they may never return.